2021
DOI: 10.3126/njog.v16i1.37609
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological spectrum of Leiomyoma – a one year retrospective study

Abstract: Aims: To analyze the histomorphology of leiomyoma in specimens received in Pathology. Methods: This is a retrospective descriptive study of histopathology database of histomorphologic spectrum of leiomyoma at Pathology Laboratory of Nobel Medical College Teaching Hospital, Biratnagar, Nepal from April 2020 to April 2021. Data for the leiomyoma were analyzed descriptively. Ethical approval was obtained from the Institutional review committee. Results: A total of 1705 histopathology specimens were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…(3,5,7,11,12) Several studies have shown a decline in the relative frequency of MCD. (1,4,6,7,14,15) However, in our study, MN was the most common PGD. Table 5 shows the common glomerular diseases encountered in the present study as compared with patterns from countries other than India.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…(3,5,7,11,12) Several studies have shown a decline in the relative frequency of MCD. (1,4,6,7,14,15) However, in our study, MN was the most common PGD. Table 5 shows the common glomerular diseases encountered in the present study as compared with patterns from countries other than India.…”
Section: Discussioncontrasting
confidence: 47%
“…21 LN is also the most common SGD seen in the Indian subcontinent. 6,7,11,12,14,15 but in present study Amyloidosis is the most common SGD.Amyloidosis accounted for 13.53% of total biopsies and 52.08% of those with SGD. The majority of renal amyloid cases were diagnosed on renal biopsies from patients with a history of tuberculosis.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation